Biocompatibility of silicon nitride produced via partial sintering & tape casting. Issue 3 (1st February 2021) - Cecen, Berivan; Topates, Gulsum; Kara, Aylin; Akbulut, Serdar Onat; Havitcioglu, Hasan; Kozaci, Leyla Didem
Abstract: The biocompatibility of silicon nitride ceramics was proven by several studies however this study is apart from the literature in the manner of production routes that are tape casting and partial sintering. We report the tape casting route was chosen and a porous structure was obtained by partial sintering technique. Tape casting brought a smooth surface to the samples. Density and pore size distribution analysis showed that the scaffolds have low density because of the porous structure. XRD and SEM analyses were carried out to reveal the phase and microstructural characteristics of porous ceramic samples. Static contact angle measurement was done for the characterization of the wettability of the scaffolds. It revealed that the surface of the scaffolds was highly hydrophilic which is a desirable characteristic for the protein and cell adhesion. The mechanical characteristics of the scaffolds were analyzed by compression tests. Human osteosarcoma cells were used for in vitro studies. Cell-proliferation and cytotoxicity were analyzed by WST-1 and LDH, respectively. The osteoblastic behavior of the cells on the surface of the scaffolds was identified by alkaline phosphatase activity. BCA analysis was used for total protein content. The BCA and ALP results showed an increasing trend which is directly correlated with cell proliferation. Cells on the surface of the silicon nitride scaffolds were visualized by SEM and fluorescence microscopy where the images supported the in vitro analysis. Therefore, porous silicon nitride scaffolds fabricated via tape casting and partial sintering were biocompatible and they are possible candidates as bone substitute elements. Graphical abstract: Image 1